Gerakan Pembaruan Pendidikan Islam: Studi Komparasi Pergerakan Islam Indonesia antara Syekh Ahmad Surkatiy dan KH Ahmad Dahlan - Umar Syarif (Institut Dirosat Islamiyah Al-Amien Prenduan, 2017)
This paper set out from the condition of muslims in Indonesia during the Dutch colonial era which filled with deviant practices such as shirk (polytheism), bid’ah (any newly invented matter that is without precedent), and khurafat (superstition). The condition is exacerbated by the Dutch government's policy that restricted Islamic education to expedite their christian mission. The appearance of Ahmad Surkati and Ahmad Dahlan with their concept of education had successfully change the condition. This paper is to find out theirIslamic education concept and to compile it, as well as to look for the implications of both in national education. This is a qualitative research. This research studies the literatures related to Ahmad Surkati and Ahmad Dahlan, in form of manuscripts or other forms. Descriptive analysis method is employed to analyze their concept.The result shows that their concept of education are both based on al-Quran and al-Sunnah with the understading the Salaf. The main purpose of their education concept are both to restore the purity of Islam, but they have slightly different focus. Ahmad Surkati focused on Arabic while Ahmad Dahlan focused on Indonesian natives. The implication of their concept are the spread of tauhid, aqidah shahih, manhaj salaf, Arabic language teaching and learning, Islamic education reform, and the spread of Al-Irsyad and Muhammadiyah schools around the nation of Indonesia.